Diarrhea associated with rotaviruses, enterotoxigenic Escherichia coli, Campylobacter, and other agents in costa rican children, 1976-1981 - Mata Jiménez, Leonardo (1983)
artículo -- Universidad de Costa Rica. Instituto de Investigaciones en Salud, 1983